Putik Mud Crab Enterprise / Mohd Ilham Yusof... [et al] - Yusof, Mohd Ilham; Mohd Saidin, Mahsidi; Tain, Jubirinika; Raubi, Viviana Priscillia (2011)
The company's name is Putik Mud Crab Enterprise. This business is about provided mud crab product that shells less crab especially in Sabah market Putik Mud Crab Enterprise actually involve in the manufacturing industry. We farm the mud crab and sell it in the local market. The reasons we choose this type of project because it has high potential in the market and we choose strategic place for this industry at No. 23, Lot 1, Block 8, Jalan Pelabuhan, Tanjung Lipat, 88000 Kota Kinabalu, Sabah. We consider the place as a strategic place because it easy to supply for local market. We suggest that we open our business on 1 January 2012. Our reason for choose this business because in Malaysia and specifically in Sabah there are no strong competitors. There are great opportunities that must be grabbing by us because a successful entrepreneur is always find and use the opportunity in front of them. As the supply on crabs especially mud crabs in Kota Kinabalu are less in competitor but are huge in market size, we are hoping that we will be one of the leading suppliers of crabs in Sabah. Meanwhile, as a new company in this arena of agriculture, we will definitely have to put more effort on the marketing as we need to achieve establishment, trust and loyal customer in buying our crabs. As one of our long run in the business, we are hoping to be able to stretch out our product by exporting crabs on targeted country. This will ensure to cost more on budget as we need more capital in order to give enough supply on our targeted market.